Global Market Pressures and the Colonial Structural Crisis: The Decline of the Sugar Industry in East Java, 1901–1939 - Salman Bahreisy; Haryono Rinardi; Yety Rochwulaningsih (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Global Market Pressures and the Colonial Structural Crisis: The Decline of the Sugar Industry in East Java 1901–1939 is the subject of this articles analysis. The Agrarische Wet and Suiker Wet of 1870 which abolished the system of forced cultivation and spurred an explosion of private capital and technological advancement marked the beginning of this industrial revolution. Coffee was displaced by sugar as the Dutch East Indies main export good as a result of these policies. This study looks at how the Panarukan region was incorporated into the global economy as a supplier of commodities for the core nation which in turn created a structure of dependency for the local community using Dependency Theory as a lens. Using colonial texts like the Staatsblad and the Jaarboek voor suikerfabrikanten a historical approach that includes heuristics source criticism interpretation and historiography is used. The results of the study show that the Brantas River Valleys alluvial soil fertility and contemporary irrigation infrastructure like the Sampean Dam supported East Javas strategic location. However this industrys prosperity concealed structural weaknesses that culminated in a global decline in sugar prices and widespread layoffs that affected about 800000 workers during the Great Depression of 1929. In order to survive the Panarukan people used socioeconomic adaptation to turn sugarcane fields into food crops like rice tobacco or secondary crops. The originality of this study emphasizes that the 1929 crisis was a turning point that revealed the weaknesses in the colonial dependency system rather than just an economic downturn. The demise of Panarukans sugar industry provides a striking example of how exploitative capitalist prosperity is extremely susceptible to outside shocks from the world market.